2016
DOI: 10.1037/pspp0000063
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of testosterone and cortisol is associated with attained status in male executives.

Abstract: Are hormone levels associated with the attainment of social status? Although endogenous testosterone predicts status-seeking social behaviors, research suggests that the stress hormone cortisol may inhibit testosterone’s effects. Thus, individuals with both high testosterone and low cortisol may be especially likely to occupy high-status positions in social hierarchies while individuals with high testosterone and high cortisol may not. We tested this hypothesis by recruiting a sample of real executives and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 79 publications
6
60
0
3
Order By: Relevance
“…shown that cortisol and testosterone jointly interact to influence attained status in male executives (Sherman et al, 2016). In another study, Mehta and Josephs (2010) …”
Section: Interactions Within Biological Strandsmentioning
confidence: 95%
“…shown that cortisol and testosterone jointly interact to influence attained status in male executives (Sherman et al, 2016). In another study, Mehta and Josephs (2010) …”
Section: Interactions Within Biological Strandsmentioning
confidence: 95%
“…Recently, a more nuanced perspective on the link between testosterone and status attainment in humans has begun to emerge. There is growing evidence that the HPG axis acts in concert with the hypothalamic-pituitary-adrenal (HPA) stress axis to regulate status attainment within groups (11,17). The HPA axis secretes the steroid hormone cortisol in response to stress and anxiety; thus interactions between the HPG and HPA axes can be observed by measuring testosterone and cortisol simultaneously.…”
mentioning
confidence: 99%
“…For instance, individuals high in testosterone and low in cortisol have a greater number of subordinates, a measure of attained status (17); are perceived as more dominant leaders (18); are more respected by their peers (19); are more popular within their social networks (20); and engage in more competitive behavior as well as risktaking (18,21), a behavioral strategy associated with the attainment of social status (22,23).…”
mentioning
confidence: 99%
“…Together this hormonal combination suggests power posing leaves a subject feeling dominant and powerful, while also less stressed. A potent hormonal interaction, greater testosterone and lower cortisol has been linked to hierarchical position and status for business executives, suggesting greater leadership potential (Sherman, Lerner, Josephs, Renshon, & Gross, 2016). …”
Section: Introductionmentioning
confidence: 99%